The Effect of Scramble Media on Improving The Ability to Compose Simple Sentences of Deaf Students - Putri, Novia Kelana; Priyono, Priyono; Supratiwi, Mahardika (Jurnal Penelitian dan Pengembangan Pendidikan Luar Biasa, 2024)
This study aims to determine the effect of Scramble media on improving the ability to compose simple sentences for deaf students in class IV B at Sekolah Khusus Tunarungu Surakarta. This study used an experimental approach in the form of pre-post experimental design one group pre test-post test design. The subjects in this study were all deaf students totaling 6 students. This study uses a sampling technique that is non-probability sampling. The technique used in data collection is a written test in the form of multiple choice objective tests. Data analysis technique used is non-parametric statistics with Wilcoxon Sign Rank Test. The results of descriptive analysis obtained the average value of the post test is greater than the pre-test value, namely 57.80 to 88.33. Furthermore, the results of the analysis of the Wilcoxon Sign Rank Test showed that the Zhitung value was -2.214 and the Asymp- Sig (2-tailed) was 0.027 with a significance level (α) of 0.05 or 5%. It can be concluded that Asymp-Sig (2-tailed) is smaller than the significance level or 0.027